2021
DOI: 10.1007/s10029-021-02481-x
|View full text |Cite
|
Sign up to set email alerts
|

Extended-duration thromboprophylaxis after ventral hernia repair: a risk model to predict venous thrombotic events after hospital discharge

Abstract: Background Venous thromboembolism (VTE) is a major source of morbidity and mortality after ventral hernia surgery, but the risk of VTE after discharge has not been reported. Study design Data from the American College of Surgeons-National Surgical Quality Improvement Program (ACS-NSQIP) were used to investigate the risk of post-discharge VTE. Current procedural terminology (CPT) codes identified all reported patients who underwent ventral hernia repair fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Additional risk factors at 1 year were discharge to extended care facilities, age older than 64 years, index admission operation, and hospital length of stay >7 days 45 . Extended VTE risk has also been documented in a variety of general surgical and surgical oncological conditions, including patients undergoing surgery for inflammatory bowel disease, 62,63 ventral hernia, 64 and abdominal/pelvic cancer, 65 and in mixed surgical populations 52 …”
Section: Current Management Strategies For the Prevention Of Vte In T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additional risk factors at 1 year were discharge to extended care facilities, age older than 64 years, index admission operation, and hospital length of stay >7 days 45 . Extended VTE risk has also been documented in a variety of general surgical and surgical oncological conditions, including patients undergoing surgery for inflammatory bowel disease, 62,63 ventral hernia, 64 and abdominal/pelvic cancer, 65 and in mixed surgical populations 52 …”
Section: Current Management Strategies For the Prevention Of Vte In T...mentioning
confidence: 99%
“…Additional risk factors at 1 year were discharge to extended care facilities, age older than 64 years, index admission operation, and hospital length of stay >7 days. 45 Extended VTE risk has also been documented in a variety of general surgical and surgical oncological conditions, including patients undergoing surgery for inflammatory bowel disease, 62,63 ventral hernia, 64 and abdominal/pelvic cancer, 65 and in mixed surgical populations. 52 Assessed two difference doses of dabigatran daily vs. enoxaparin daily for THA; no difference in overall VTE or death between the three groups and no difference in major bleeding Eriksson et al, 55 2008 Prospective, randomized control Daily rivaroxaban was found to reduce total VTE more effectively than daily LMWH after total hip replacement (0.2% vs. 2%, p < 0.001) Lassen et al, 56 2008 Prospective, randomized control Daily rivaroxaban was found to reduce total VTE more effectively than daily LMWH after total knee replacement (1% vs. 2.6%, p = 0.005) Raskob et al, 57 2012 Pooled data meta-analysis Twice-daily extended duration apixaban demonstrated reduced VTE incidence following total knee or hip replacement compared with daily LMWH (0.7% vs. 1.5%, p = 0.001) Anderson et al, 58 2013 Prospective, randomized control Following total hip replacement, patients were given LMWH or aspirin for 28 d following discharge without a significant difference in rates of either VTE or major bleeding Haac et al, 33 2020 Prospective, randomized control Patients with pelvic or extremity fractures were given either LWMH twice daily or aspirin twice daily upon discharge.…”
Section: Extended/outpatient Thromboprophylaxismentioning
confidence: 99%